The Images and The Struggle of The 2018 Central-Java Local Government Election Reporting Meaning in Online Media - Parwaningtiyas, Anung Anindita; Mardikantoro, Hari Bakti; Joko Santoso, Bernadus Wahyudi (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
The role of online media is really essential in society because it fosters and encourages the public opinion. Therefore, online media could be the most effective interest mean to achieve certain massive purposes, including the reports of certain actor's images. It allows social actor's images to not being reported objectively but instead processed and managed. Thus, it could be said there is a correlation between the language and the domination in the discourse practice to create ideologies with certain purposes. The point, the mass media has its specific powers to control its information display so its neutrality in the mass media is doubtful. So as this research, the images of social actorÃ¢â‚¬â„¢s images, the candidate of Central-Java election 2018, become the focused problems to analyze by Theo van Leeuwen theory. The data sample was obtained from the report discourse in online mass media, such as Kumparan.com, Tribunnews.com, and Sindonews.com about the Central-Java Election 2018, from April-June 2018. The analysis was based on the deletion strategy in which covered suppression and backgrounding. The results showed that Kumparan.com tended to apply suppression in merging the social actors, Ganjar Pranowo-Taj Yasin and backgrounding in the form of a phrase Ã¢â‚¬Å“politikus PDIP, mantan anggota DPR RI yang diperiksa KPKÃ¢â‚¬Â. (The PDIP politician, the ex of the House whom is investigated by Corruption Eradication Comission). Meanwhile, Tribunnews.com applied backgrounding in the form of Ã¢â‚¬Å“sang petahanaÃ¢â‚¬Â or Ã¢â‚¬Å“incumbentÃ¢â‚¬Â, meanwhile Sindonews.com did not either put certain social actors in advantage nor marginalize them.